Ultra-wideband E-shaped dielectric resonator antenna fed by coaxial probe and trapezoidal conductor. Issue 2 (3rd April 2021) - Abushakra, Feras; Al-Zoubi, Asem; Uluer, Ismail; Hawatmeh, Derar
ABSTRACT: In this paper, an enhanced performance E-shaped dielectric resonator antenna (DRA) with a relative permittivity of 9.2 is introduced. The new design offers a very wide operating range that extends from 3.85 to 13.3 GHz, with a fractional bandwidth of 110%. The antenna shows a stable gain (5.0–7.5 dBi) with an average efficiency of 95% across the frequency of interest. Furthermore, the antenna presents a compact volume with 30 × 40 × 11.3 mm 3 dimensions, which makes it an excellent candidate for many wireless applications. The proposed design is simulated using two full-wave simulators, HFSS and CST MWS, and then measured to validate the proposed design. The simulation and measurement show very good agreement over the extended operating frequency.